calculate first and second differences of y=-5(x-2)squared+3
The first part of the question A) ; given the following graph and the values of h and h, h=2,k=3 Determine its equations (there is a picture of a parabola with given points A(0,2); out of this i got its equation to be y=-5(x-2)squared+3
The second part(b) says to calculate the first and second differences of the equation
y=-5(x-2)squared+3
im going to assume that by difference you mean derivative.
1st derivative: -10(x - 2) via:
d/dx of z^n = n*z^(n-1)
i used z=(x-2) and n=2
the 3 gets dropped because the slope of a constant is 0.
simplify to y' = -10x + 20
the 2nd derivative is y''=-10
via the slope of y' is always -10.
hope that helps